Sphingosine and FTY720 are potent inhibitors of the transient receptor potential melastatin 7 (TRPM7) channels. (25th February 2013) - Qin, Xin; Yue, Zhichao; Sun, Baonan; Yang, Wenzhong; Xie, Jia; Ni, Eric; Feng, Yi; Mahmood, Rafat; Zhang, Yanhui; Yue, Lixia
<x xml:space="preserve">Abstract</x> Background and Purpose Transient receptor potential melastatin 7 (TRPM7) is a unique channel kinase which is crucial for various physiological functions. However, the mechanism by which TRPM7 is gated and modulated is not fully understood. To better understand how modulation of TRPM7 may impact biological processes, we investigated if TRPM7 can be regulated by the phospholipids sphingosine (SPH) and sphingosine‐1‐phosphate (S1P), two potent bioactive sphingolipids that mediate a variety of physiological functions. Moreover, we also tested the effects of the structural analogues of SPH, N, N‐dimethyl‐D‐erythro‐sphingosine (DMS), ceramides and FTY720 on TRPM7. Experimental Approach HEK293 cells stably expressing TRPM7 were used for whole‐cell, single‐channel and macropatch current recordings. Cardiac fibroblasts were used for native TRPM7 current recording. Key Results SPH potently inhibited TRPM7 in a concentration‐dependent manner, whereas S1P and other ceramides did not produce noticeable effects. DMS also markedly inhibited TRPM7. Moreover, FTY720, an immunosuppressant and the first oral drug for treatment of multiple sclerosis, inhibited TRPM7 with a similar potency to that of SPH. In contrast, FTY720‐P has no effect on TRPM7. It appears that SPH and FTY720 inhibit TRPM7 by reducing channel open probability. Furthermore, endogenous TRPM7 in cardiac fibroblasts was markedly inhibited by SPH, DMS and FTY720. Conclusions and Implications This is the first study demonstrating that SPH and FTY720 are potent inhibitors of TRPM7. Our results not only provide a new modulation mechanism of TRPM7, but also suggest that TRPM7 may serve as a direct target of SPH and FTY720, thereby mediating S1P‐independent physiological/pathological functions of SPH and FTY720. Linked Article This article is commented on by Rohacs, pp. 1291–1293 of this issue. To view this commentary visit http://dx.doi.org/10.1111/bph.12070